Lubiąskie rękopisy muzyczne z XIII wieku na tle badań nad skryptoriami cystersów. Nutacja diastematyczna - Wałkówski, Andrzej (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The present paper concerns the manuscripts that have diastematic notation. Manuscripts with this notation prevail over codices with cheironomic notation, which probably stems from its popularity in the 13th century, and from adopted by the Cistercians music solutions used in the Metz Cathedral. I will discuss selected music manuscripts of Lubiąż from the 13th century in terms of paleographical analysis, by identifying hands, determining the canon of writings and datation. Simultaneously, I evade the musicological and artistic analysis of tunes contained in the analyzed codices. I am not an expert in the field of music. Hence, there is such a limitation of purposes of my study. By the end of the 13th century, in the scriptorium of Lubiąż there had been ten preserved music manuscripts with diastematic notation. Two antiphonary and two graduals come from the first half of the13th century, and had been written by copyist James of Lubiąż, mentioned in the Obituary of Lubiąż. He created only in fragments these two graduals. It should be noted that he also prepared four documents from the years 1212-1222. His four written codices also come from this time. In addition, he was the proofreader of a fragment of a book Liber Usuum Cisterciensium. Except for him, we meet eight hands, marked with the letters from A to H of anonymous writers. Copyist James and hands A and B were using romance-gothic writing and they worked until 1234. In addition, arms C and D were active in the years 1235-1253 and they were using romancegothic vista. Hands E, F and H were using fully formed gothic writing. The activity of the first of them occurred in the second half of the 13th century, and the activity of the rest appeared at the end of this century